Loyalitas Pengguna Kartu Xl yang dimediasi oleh Kepuasan Pelanggan dengan Prediktor Customer Relationship Management dan Customer Bonding di Kota Banda Aceh - Amira, Faiza; Utami, Sorayanti (Manajemen Inovasi Bisnis dan Strategi, 2025)
Using customer satisfaction as an intervening variable, this study examines how customer loyalty is affected by customer relationship management (CRM) and customer bonding among Banda Aceh's XL card users. Purposive sampling was used to select 190 participants in total, and structured questionnaires were used to collect the data. The Statistical Product and Service Solutions (SPSS) software was used in the study to assess the correlations between the variables. The results show that customer happiness and loyalty are directly and favorably impacted by both CRM and customer bonding. Additionally, a major factor in increasing client loyalty is customer satisfaction. These findings also demonstrate that, when mediated by customer happiness, CRM and customer bonding have a significant but indirect impact on customerloyalty.